Effect of a blended learning design in an undergraduate nursing electrocardiogram course: A quasi‐experimental study - Li Jiang; Duoduo Wang; Jie Yan; Min Yang (Wiley, 2023)
Abstract Aim The study aimed to explore learning achievement and students' satisfaction with a blended learning (BL) electrocardiogram (ECG) education programme in undergraduate nursing education. Design This was a quasi‐experimental post‐test design. Methods The study was conducted during semester one of the academic year 2020/2021. Participants were divided into two groups: the BL group and face‐to‐face (FTF) group. The BL group received the newly designed BL programme. The FTF group received the traditional learning methods. Post‐test measures of the study variables such as knowledge, study time and satisfaction were conducted. Chi‐square (χ2) test was used to evaluate categorical variables. The Mann-Whitney test was used to analyse continuous variables. Results Participants in BL group had significantly higher scores in ECG interpretation and total score. No significant differences in foundational knowledge between the two groups were found. Study time was significantly longer in the BL group. Regarding satisfaction, significant differences were found in structure rationality and promotion of self‐learning.